2003
DOI: 10.1007/s00436-003-0943-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on sex-related inflammatory reactions in mice infected with Schistosoma mansoni

Abstract: The aim of this study was to investigate the contribution of the sex of both the parasite and the host to the inflammatory response induced in unisexual infections of Schistosoma mansoni in mice. Organ weight, cell count and the delayed type hypersensitivity reaction were used as tools in this comparative study. The inflammatory reactions differed as a function of the sex of both the host and the parasite. Female mice showed a stronger inflammatory reaction to schistosome infection than males, while male schis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 25 publications
3
56
0
Order By: Relevance
“…Some of the results obtained in the literature also showed that protection by male parasite is higher than by female parasite: In the synthesis of Dean (1983), Table V, on the 18 results showing a reduction of more than 20%, 12 were obtained from male primo-infections and only 6 from female ones; in the synthesis of Moné and Boissier (2004), Table II, on the 17 results showing a reduction of more than 20%, 12 were obtained from male primo-infections and only 5 from female ones. The difference between male and female protectivities could originate from the higher inflammatory reaction induced by males compared to females in unisexual infections (Boissier et al 2003). The significant increase in the organ weights between mass and trickle infections that we observed only in male infections seems to confirm this and could be linked to a difference in the quantity and/or the quality between the male and female parasite antigens.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Some of the results obtained in the literature also showed that protection by male parasite is higher than by female parasite: In the synthesis of Dean (1983), Table V, on the 18 results showing a reduction of more than 20%, 12 were obtained from male primo-infections and only 6 from female ones; in the synthesis of Moné and Boissier (2004), Table II, on the 17 results showing a reduction of more than 20%, 12 were obtained from male primo-infections and only 5 from female ones. The difference between male and female protectivities could originate from the higher inflammatory reaction induced by males compared to females in unisexual infections (Boissier et al 2003). The significant increase in the organ weights between mass and trickle infections that we observed only in male infections seems to confirm this and could be linked to a difference in the quantity and/or the quality between the male and female parasite antigens.…”
Section: Discussionsupporting
confidence: 77%
“…The significant increase in the organ weights between mass and trickle infections that we observed only in male infections seems to confirm this and could be linked to a difference in the quantity and/or the quality between the male and female parasite antigens. This antigenic difference between both sexes could be at the origin of the different protective effects between male and female schistosomes (Boissier et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are differences between the sexes in the induction of genes associated with toll-like receptor (TLR) pathways and antiviral type I interferon (IFN) responses [1,5,6]; cells from females can show a 10-fold greater level of expression than cells from males [6]. Studies of both humans and rodents illustrate that the number and activity of innate immune cells, including monocytes, macrophages, and dendritic cells (DCs) as well as inflammatory immune responses in general are higher in females than males [79]. …”
Section: Innate and Adaptive Immune Responses Differ Between The Sexesmentioning
confidence: 99%
“…Thereafter, these markers were tested on male and female of the three strains (Table 1). Detailed methods employed for molluscan and rodent infections were described previously [20,21]. …”
Section: Methodsmentioning
confidence: 99%